Jogos teatrais introdutórios na escola: um caminho metodológico no processo de ensino e aprendizado de alunos de Mazagão - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The theatrical game as a methodology is a vast field to be explored and an important tool for the insertion of theatrical language within is a vast field to be explored and an important tool for the insertion of theatrical language within the classroom space. Thus, this work aimed to analyze the introductory theater games, as a methodological approach applied in the classroom at the Manoel Queiroz Benjamin State School. For this, the author Viola Spolin was used as a theoretical reference, which outlined such methodology. With this, a four-day project was created to apply this methodology with students in the fifth year of elementary school at the school. Questions of concentration, communication, interpersonal relationships, body expression, among others, were addressed in this project. In this work I also report how my first contacts with such an artistic language occurred and what led to the choice of such a theme. In addition to addressing in a bibliographical way the trajectory that theater teaching has taken throughout the history of Brazilian education.
Keywords: Jogo Teatral; Aprendizado; Metodologia; CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO; ODS 3 – Saúde e bem-estar; ODS 4 – Educação de qualidade